Environmental degradation of NR latex gloves in a composting environment - Ikram A (Journal of Rubber Research, 2003)
The environmental degradation of NR latex gloves in a composting environment was studied using a matrix of dried leaves, cattle manure and soil in holed bins. In treatments containing 9;of the test material, NR glove pieces retained 25;-27;of their initial weights after 24 weeks under conditions of 40;-55;moisture and a weekly turning over. Nitrile and plasticed PVC (vinyl) glove pieces did not degrade under the conditions employed. The disintegration rate of NR glove materials were lower (53;initial weight remaining) when the holes in the bins were sealed, implying the importance of adequate access of air to the samples. The appropriateness of pile dimensions, moisture, aeration and temperature as controlling factors in composing of NR latex gloves is discussed.
Keywords: Biodegradation; Composting; Degradation; Environment; Nitrile gloves; NR latex gloves; PVC gloves